Passion for work and job satisfaction in sports coaches: the mediating role of flow experiences - Peixoto, E. M.; Palma, B. P.; Romano, A. R.; Vieira, T. C. H.; Galatti, L. R. (International Sport Coaching Journal, 2024)
Sports coaching is a volatile and stressful career that may impact professionals` well-being. Thus, variables that can promote coaches` job satisfaction need to be investigated. Based on the hypotheses of potential effects of passion for work (e.g., subjects` inclination for an activity, which becomes integrated into the person`s identity) on flow experience (e.g., positive and transient state that can promote total absorption, enjoyment, and intrinsic motivation) and job satisfaction (e.g., state of positive emotions, resulting from continuous experiences in the workplace), this research aimed to assess the association among the dualistic model of passion (harmonious and obsessive), flow, and job satisfaction in sports coaches. The sample consisted of 172 Brazilian coaches from different sports (69.60% male). Structural equation modeling demonstrated that both forms of passion were positively associated with absorption and intrinsic motivation experience; however, only harmonious passion showed a significant relationship with enjoyment and job satisfaction. Furthermore, a mediating role of flow (work enjoyment and intrinsic motivation) in the relationship between harmonious passion and coaches` job satisfaction was observed. The results suggest that coaches who demonstrate harmonious passion for the profession tend to have a greater perception of positive experiences at work and feel more satisfied with these activities.